Integration of business processes applying service-oriented architecture (SOA) - Peralta-Ascue, Marleny (2017)
This article aims to integrate business processes in the field of small and medium-sized enterprises (SMEs, or PYMES for its acronym in Spanish). The integration will be achieved through the development of web applications based on integration architectures, such as Service Oriented Architecture (SOA) and Web services. The integration of business processes allows companies to join their business objectives, as well as optimize processes based on the concept of service. To achieve an optimal communication between companies and their clients through the services, various web standards were used, including: XML as standard format to describe the data; SOAP as data exchange protocol; WSDL to describe available services; and finally UDDI to publish information and check what web services are available.